Intracranial thrombosis associated with MSSA bacteraemia in the setting of influenza A. Issue 4 (22nd April 2021) - Raghavan, Sairam; Gonakoti, Sriram; Parra-Rodriguez, Luis
Abstract : The authors present a case of a 42-year-old previously healthy man who presented in sepsis, with right lateral gaze palsy. He was found to have bilateral cavernous sinus thrombosis (CST) and bilateral internal jugular thrombosis in the setting of Staphylococcus aureus bacteraemia. The patient was successfully treated and recovered from his illness after a protracted stay in the medical intensive care unit. We go over the treatment course and follow-up of this patient and discuss the need to have a high degree of clinical suspicion for CST and suppurative thrombophlebitis of the internal jugular veins. We also discuss the possible role of the Panton-Valentine leukocidin in causing thrombotic complications of S. aureus bacteraemia.